Effects of Quercetin on the Efficacy of Various Chemotherapeutic Drugs in Cervical Cancer Cells - Xu W; Xie S; Chen X; Pan S; Qian H; Zhu X (Dove Medical Press, 2021)
Wenbin Xu,* Shangdan Xie,* Xin Chen, Shuya Pan, Hongfei Qian, Xueqiong Zhu Center of Uterine Cancer Diagnosis & Therapy Research of Zhejiang Province, Department of Obstetrics and Gynecology, The Second Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, 325027, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xueqiong ZhuCenter of Uterine Cancer Diagnosis & Therapy Research of Zhejiang Province, Department of Obstetrics and Gynecology, The Second Affiliated Hospital of Wenzhou Medical University, No. 109 Xueyuan Xi Road, Wenzhou, Zhejiang, 325027, People’s Republic of ChinaTel +86 577 88002796 (office)Fax +86 577 88002796Email zjwzzxq@163.comPurpose: This study aimed to investigate the effects of quercetin on the efficacy of various chemotherapeutic drugs in cervical cancer cells.Methods: All drug experiments were performed in HeLa and SiHa cells. The cell viability was detected by Cell Counting Kit-8 assay, and cell proliferation was estimated by bromodeoxyuridine assay. CompuSyn software was utilized to calculate the combination index (CI) and evaluate the synergistic or antagonistic effect of quercetin with cisplatin, paclitaxel, 5-fluorouracil and doxorubicin on cell viability. Cell migration and invasion abilities were detected by transwell assays, and cell apoptosis was measured by flow cytometry. The expression levels of matrix metallopeptidase 2 (MMP2), ezrin, P-glycoprotein (P-Gp) and methyltransferase-like 3 (METTL3) protein treated with various drugs were analyzed by Western blotting.Results: Quercetin inhibited the viability of HeLa and SiHa cells in a dose- and time-dependent manner. The CI values of quercetin with cisplatin, paclitaxel, 5-fluorouracil and doxorubicin were < 1, > 1, > 1 and > 1, respectively. The effect of combination of quercetin and cisplatin on cell proliferation was stronger than their individual effects. Co-treatment group could inhibit more cell migration and invasion in contrast to single-drug group. Besides, quercetin combined with cisplatin group induced more cell apoptosis in contrast to single-drug group. The results of Western blotting showed that the expression levels of MMP2, ezrin, P-Gp and METTL3 in co-treatment group were lower than in cisplatin group, respectively.Conclusion: Quercetin and cisplatin had synergistic inhibitory effect on cervical cancer cells. Quercetin might enhance the antitumor effect of cisplatin via inhibiting proliferation, migration and invasion and elevating apoptosis through weakening MMP2, ezrin, METTL3 and P-Gp expression of cancer cells.Keywords: quercetin, cisplatin, cervical cancer, chemosensitivity